TAHAP KOLESTEROL HDL DALAM KALANGAN PELAJAR OBES DI SEKOLAH MENENGAH - Syed Kamaruzaman Syed Ali; Rosnah Ismail; Raji Subramanian (Jurnal Internasional Manajemen Pendidikan, 2010)
This research was done to identify the cholesterol level among obese students. The sample comprised 54 students (B=29; G=25) identified as obese. They were aged between 13- 19 and studied in secondary school in Kuala Kangsar District of Perak. The ‘reflotron’  machines was used to gather the lipid parameter from the subjects. The data were processed using SPSS version 11.0 to answer the research question. The cholesterol level of the sample was found to be low to moderate. No significant differences between boys and girls in term of cholesterol level.